IMPLEMENTASI METODE AGILE SCRUM PADA PERANCANGAN APLIKASI PENGECEKAN PENYAKIT DIABETES BEDASARKAN ASSESMENT - Ranggi Praharaningtyas Aji; Argiyan Dwi Pritama; Banu Dwi Putranto; Darso Darso (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2024)
Technological developments in Indonesia and the world show very rapid development, almost all aspects of life have been digitized, even in the health sector. Diabetes is a chronic, chronic disease that often occurs as a result of disturbances in the body's metabolism which are often found with excessive blood sugar levels. The cause is due to changes in lifestyle, including frequent consumption of ready-to-eat food and sweet foods/drinks, smoking and alcoholic drinks. These changes and habits not only trigger diabetes mellitus but also other non-communicable diseases such as cardiovascular disease. Predictions about diabetes can be produced by collecting information about diabetes sufferers which is stored in a database, after which the data is processed and the results will form a certain pattern, where the final results can be used to diagnose diabetes. The aim of this research is to design a diabetes checking application using the Agile Scrum method which users use to check how many percent are affected by diabetes by answering several questions that have been prepared by the system. The results will come out from the answers to these questions, how many percent are affected by diabetes and suggestions are also provided to overcome them beforehand. go to a health facility for further check-ups.